Project accept (HPTN 043): A community-based intervention to reduce HIV incidence in populations at risk for HIV in sub-Saharan Africa and Thailand - Gertrude Khumalo-Sakutukwa (2018)
Background: Changing community norms to increase awareness of HIV status and reduce HIV-related stigma has the potential to reduce the incidence of HIV-1 infection in the developing world. Methods: We developed and implemented a multilevel intervention providing community-based HIV mobile voluntary counseling and testing, community mobilization, and posttest support services. Forty-eight communities in Tanzania, Zimbabwe, South Africa, and Thailand were randomized to receive the intervention or clinic-based standard voluntary counseling and testing (VCT), the comparison condition. We monitored utilization of community-based HIV mobile voluntary counseling and testing and clinic-based standard VCT by community of residence at 3 sites, which was used to assess differential uptake. We also developed quality assurance procedures to evaluate staff fidelity to the intervention. Findings: In the first year of the study, a 4-fold increase in testing was observed in the intervention versus comparison communities. We also found an overall 95% adherence to intervention components. Study outcomes, including prevalence of recent HIV infection and community-level HIV stigma, will be assessed after 3 years of intervention. Conclusions: The provision of mobile services, combined with appropriate support activities, may have significant effects on utilization of voluntary counseling and testing. These findings also provide early support for community mobilization as a strategy for increasing testing rates. Copyright © 2008 by Lippincott Williams & Wilkins.